Supporting frontline workers in the biodiversity crisis by empowering and enabling practitioners to embrace conservation evidence - Steven J. Cooke; Kevin A. Adeli; Trina Rytwinski; Andrew N. Kadykalo; Jennifer F. Provencher; Vivian M. Nguyen; Joseph R. Bennett; Christina M. Davy; Rachel T. Buxton; Dalal E. L. Hanna; Nathan Young; Jesse C. Vermaire; et al. (Socio-Ecological Practice Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Proterozoic highly siderophile element enrichment of the Kaapvaal cratonic Archean mantle - Nadine P. Cooper; D. Graham Pearson; Andreas Auer; Tristan Bongartz; Yannick Bussweiler; Mario Fischer-Gödde; Max Hellers; Geoffrey Howarth; Andrew J. Locock; Ambre Luguet; Carsten Münker; Thomas Stachel; et al. (Chemical Geology, 2026)

Twelve strategies for realizing the promise of ecopracticology - Steven J. Cooke; Marco Carlotti; Kgosietsile Velempini; Nathan Heavers; Zhifang Wang; Zoe Moula; Qinghe Hou; Andrew Howarth; Meagan Harper; Andrew N. Kadykalo; Yasuhisa Kondo; Yue Che; et al. (Socio-Ecological Practice Research, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Population genomics of Mediterranean oat (A. sativa) reveals high genetic diversity and three loci for heading date - F. J. Canales; G. Montilla-Bascón; W. A. Bekele; C. J. Howarth; T. Langdon; N. Rispail; N. A. Tinker; E. Prats (Theoretical and Applied Genetics, 2021)
Key message Genomic analysis of Mediterranean oats reveals high genetic diversity and three loci for adaptation to this environment. This information together with phenotyping and passport data, gathered in an interactive map, will be a vital resource for oat genetic improvement. Abstract During the twentieth century, oat landraces have increasingly been replaced by modern cultivars, resulting in loss of genetic diversity. However, landraces have considerable potential to improve disease and abiotic stress tolerance and may outperform cultivars under low input systems. In this work, we assembled a panel of 669 oat landraces from Mediterranean rim and 40 cultivated oat varieties and performed the first large-scale population genetic analysis of both red and white oat types of Mediterranean origin. We created a public database associated with an interactive map to visualize information for each accession. The oat collection was genotyped with 17,288 single-nucleotide polymorphism (SNP) loci to evaluate population structure and linkage disequilibrium (LD); to perform a genome-wide association study (GWAs) for heading date, a key character closely correlated with performance in this drought-prone area. Population genetic analysis using both structure and PCA distinguished two main groups composed of the red and white oats, respectively. The white oat group was further divided into two subgroups. LD decay was slower within white lines in linkage groups Mrg01, 02, 04, 12, 13, 15, 23, 33, whereas it was slower within red lines in Mrg03, 05, 06, 11, 21, 24, and 28. Association analysis showed several significant markers associated with heading date on linkage group Mrg13 in white oats and on Mrg01 and Mrg08 in red oats.

Multidisciplinary Scientific Cruise to the Rio Grande Rise - Luigi Jovane; James R. Hein; Isobel A. Yeo; Mariana Benites; Natascha M. Bergo; Paulo V. F. Corrêa; Daniel M. Couto; Ayrton D. Guimarães; Sarah A. Howarth; Henrique R. Miguel; Kira L. Mizell; Denise S. Moura; et al. (Frontiers in Marine Science, 2019)

Tsunami runup and tide-gauge observations from the 14 November 2016 M7.8 Kaikōura earthquake, New Zealand - William Power; Kate Clark; Darren N. King; Jose Borrero; Jamie Howarth; Emily M. Lane; Derek Goring; James Goff; Catherine Chagué-Goff; James Williams; Catherine Reid; Colin Whittaker; et al. (Pure and Applied Geophysics, 2017)

Dietary inclusions of dried macroalgae meal in formulated diets improve the growth of greenlip abalone (Haliotis laevigata) - Matthew S. Bansemer; Jian G. Qin; James O. Harris; Duong N. Duong; Krishna-Lee Currie; Gordon S. Howarth; David A. J. Stone (Journal of Applied Phycology, 2016)

High-density marker profiling confirms ancestral genomes of Avena species and identifies D-genome chromosomes of hexaploid oat - Honghai Yan; Wubishet A. Bekele; Charlene P. Wight; Yuanying Peng; Tim Langdon; Robert G. Latta; Yong-Bi Fu; Axel Diederichsen; Catherine J. Howarth; Eric N. Jellen; Brian Boyle; Yuming Wei; et al. (Theoretical and Applied Genetics, 2016)

Dapagliflozin reduces the amplitude of shortening and Ca2+ transient in ventricular myocytes from streptozotocin-induced diabetic rats - N. N. Hamouda; V. Sydorenko; M. A. Qureshi; J. M. Alkaabi; M. Oz; F. C. Howarth (Molecular and Cellular Biochemistry, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

Genetic Diversity and Population Structure Among Oat Cultivars and Landraces - G. Montilla-Bascón; J. Sánchez-Martín; N. Rispail; D. Rubiales; L. Mur; T. Langdon; I. Griffiths; C. Howarth; E. Prats (Plant Molecular Biology Reporter, 2013)

Evidence Supporting the use of Probiotics for the Prevention and Treatment of Chemotherapy-Induced Intestinal Mucositis - Luca D. Prisciandaro; Mark S. Geier; Ross N. Butler; Adrian G. Cummins; Gordon S. Howarth (Critical Reviews in Food Science and Nutrition, 2011)

Altered gene expression may underlie prolonged duration of the QT interval and ventricular action potential in streptozotocin-induced diabetic rat heart - F. C. Howarth; M. Jacobson; M. A. Qureshi; M. Shafiullah; R. S. Hameed; E. Zilahi; A. Al Haj; N. Nowotny; E. Adeghate (Molecular and Cellular Biochemistry, 2009)

Effects of streptozotocin-induced diabetes on connexin43 mRNA and protein expression in ventricular muscle - F. C. Howarth; N. J. Chandler; S. Kharche; J. O. Tellez; I. D. Greener; T. T. Yamanushi; R. Billeter; M. R. Boyett; H. Zhang; H. Dobrzynski (Molecular and Cellular Biochemistry, 2008)

Development of genic-microsatellite markers for sorghum staygreen QTL using a comparative genomic approach with rice - G. Srinivas; K. Satish; S. Murali Mohan; R. Nagaraja Reddy; R. Madhusudhana; D. Balakrishna; B. Venkatesh Bhat; C. J. Howarth; N. Seetharama (Theoretical and Applied Genetics, 2008)

Altered expression of gap junction connexin proteins may partly underlie heart rhythm disturbances in the streptozotocin-induced diabetic rat heart - F. C. Howarth; N. Nowotny; E. Zilahi; M. A. El Haj; M. Lei (Molecular and Cellular Biochemistry, 2007)

Characterization of nutrient, organic carbon, and sediment loads and concentrations from the Mississippi River into the northern Gulf of Mexico - R. E. Turner; N. N. Rabalais; R. B. Alexander; G. McIsaac; R. W. Howarth (Estuaries and Coasts, 2007)

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews‐Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)
The introduction of alien, or nonindigenous, animals and plants has been identified by scientists and policy makers as a major threat to biodiversity in marine ecosystems. Although government agencies have struggled to control alien species on land and freshwater for decades with mixed success, the control of alien marine species is in its infancy. Prevention of introduction and establishment must be the first priority, but many populations of alien marine species are already well established worldwide. National and international policies leave loopholes for additional invasions to occur and provide only general guidance on how to control alien species once they are established. To address this issue, a multinational group of 25 scientists and attorneys convened in 1998 to examine options for controlling established populations of alien marine species. The discussions resulted in a framework for control of alien marine species to provide decision‐making guidance to policymakers, managers, scientists, and other stakeholders. The framework consists of seven basic steps: (1) establish the nature and magnitude of the problem, (2) set objectives, (3) consider the full range of alternatives, (4) determine risk, (5) reduce risk, (6) assess benefits versus risks, and ( 7) monitor the situation. This framework can provide guidance for control efforts under the existing patchwork of national laws and can help provide a foundation for international cooperation.

The Control of Biological Invasions in the World's Oceans - N. Bax; J. T. Carlton; A. Mathews-Amos; R. L. Haedrich; F. G. Howarth; J. E. Purcell; A. Rieser; A. Gray (Conservation Biology, 2001)

Regional distribution of metallothionein and zinc in the mouse gut - C. D. Tran; R. N. Butler; J. C. Philcox; A. M. Rofe; G. S. Howarth; P. Coyle (Biological Trace Element Research, 1998)

Isolation and structural determination of a novel coenzyme from a methane-oxidizing bacterium - M. D. Collins; O. W. Howarth; P. N. Green (Archives of Microbiology, 1986)